Contribution of MDR1 gene polymorphisms on IBD predisposition and response to glucocorticoids in IBD in a Chinese population. Issue 1 (January 2015) - Yang, Qing Fan; Chen, Bai Li; Zhang, Qing Sen; Zhu, Zhen Hua; Hu, Bin; He, Yao; Gao, Xiang; Wang, Yi Ming; Hu, Pin Jin; Chen, Min Hu; Zeng, Zhi Rong
<x xml:space="preserve">Abstract</x> Objective The cornerstone of conventional treatment for inflammatory bowel disease (IBD) is glucocorticoid (GC). Single nucleotide polymorphisms (SNPs) of genes such as multidrug resistance 1 (MDR1) are related to patient's response to GC, and MDR1 polymorphisms are associated with susceptibility to IBD in Caucasians. We aimed to investigate whether the polymorphisms of five genes including MDR1 influence the response to GC in Chinese patients and the relationship between MDR1 and IBD susceptibility. Methods SNPs were selected and genotyped in 156 IBD patients treated with GC and 223 healthy controls. Patients were evaluated and classified as GC‐dependent, GC‐resistant or responsive to GC after treatment. Results The CC genotypes of rs1128503 and rs1045642 in MDR1 gene were more frequent in Crohn's disease (CD) patients who were GC‐dependent than in those responsive to GC (odds ratio [OR] 6.583, 95% confidence interval [CI] 1.760–24.628, P = 0.019 and OR 3.873, 95% CI 1.578–9.506, P = 0.009, respectively). The G allele of MDR1 rs2032582 was less frequent among CD patients than in controls (OR 0.668, 95% CI 0.484–0.921, P = 0.014). G allele carriers were also less likely to develop non‐stricturing and non‐penetrating CD (OR 0.661, 95% CI 0.462–0.946, P = 0.023) and ileocolonic CD (OR 0.669, 95% CI 0.472–0.948, P = 0.024). Conclusions Polymorphisms of MDR1 are associated with patient's GC response and a predisposition to CD in Chinese population. Further studies are needed to elucidate the role of MDR1 polymorphisms in IBD and that as genetic markers for GC response.